Selection of culture media for the production of carotenoids with antioxidant activity by Rhodotorula glutinis - Z, Gerelmaa; Ch, Zultsetseg; B, Batjargal; Ts, Rentsenkhand (Proceedings of the Mongolian Academy of Sciences, 2018)
Rhodotorula glutinis is an aerobic yeast with particular metabolic characteristic that can produce large amount of carotenoids during the stationary growth phase. Carotenoid is an important natural pigment with antioxidant properties, which is used in food, pharmaceutical and cosmetics industry as additives. The aim of this work is to study the production of carotenoid with antioxidant activity by R.glutinis R12 in different media conditions. The selected strain was cultivated in three different culture media such as YM broth, Basal and MS3 medium at 28°C for 72–120 hours. After fermentation, cells were harvested by centrifugation and freeze-dried. Carotenoid from the biomass was extracted as a mixture of DMSO, acetone and petroleum ether with a ratio of 1:2:2 and cells were ruptured using ultrasonic wave. The carotenoid content in the supernatant was measured by spectrophotometric method. The highest content of carotenoids extracted from R.glutinis R12 was 283.71µg/g dry biomass. The maximum antioxidant activity of carotenoid by DPPH assays were achieved 52.09 ± 0.4% (IC50= 536.02) and at a concentration of 600 µg ml-1. This study revealed that the R.glutinis R12 strain has the ability to produce carotenoid and has shown antioxidant activity in Basal and MS3 medium. For further study, it is necessary to investigate the improvement of carotenoid yield from R.glutinis R12 strains.